Oxford international primary english student book 1 - Miles, Liz (Oxford University Press Karachi, 2022)
The Oxford English Book serves as a comprehensive resource that may combine elements from both the anthology and workbook, providing a holistic approach to English language learning, integrating reading, writing, and language use in context.